2021
DOI: 10.3390/ma14082014
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl-Functionalized Janus Ring Siloxane: Potential Precursors to Hybrid Functional Materials

Abstract: A vinyl-functionalized all-cis-tetrasiloxycyclotetrasiloxane [ViSi(OSiMe2H)O]4 (Vi = vinyl group) Janus precursor was prepared from potassium cyclotetrasiloxane silanolate. The Janus precursor was selectively modified at its dimethylhydrosilyl groups [–SiMe2H] via the Piers–Rubinsztajn reaction to obtain a family of new tetravinyl-substituted Janus rings [ViSi(OR’)O]4 containing various functional groups in moderate yields. Remarkably, the tetravinyl groups on the structure remained intact after modification b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…[23][24][25] Also, the B(C 6 F 5 ) 3 -catalyzed Piers-Rubinsztajn reaction, a transition metal-free approach to preparing wellcontrolled branched polysiloxanes, [26][27][28][29] has recently become a powerful tool for extending hydrosilyl-substituted all-cis-T 4 with methoxybenzene derivatives. [30][31][32] All-cis-T 4 with pyrene groups obtained recently by this method were found to be selective sensors for detection of gold ions and L-cysteine. 32 Our group previously found that B(C 6 F 5 ) 3 as a Lewis acid could catalyze intramolecular cyclization of the hydrosilyl-substituted all-cis-T 4 in the presence of excess water, and several tricyclic ladder-type SQs with varied siloxane side ring sizes (named as "Bat Siloxane" with 8-8-8 or 12-8-12-membered-ring system, Scheme 1) were synthesized.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[23][24][25] Also, the B(C 6 F 5 ) 3 -catalyzed Piers-Rubinsztajn reaction, a transition metal-free approach to preparing wellcontrolled branched polysiloxanes, [26][27][28][29] has recently become a powerful tool for extending hydrosilyl-substituted all-cis-T 4 with methoxybenzene derivatives. [30][31][32] All-cis-T 4 with pyrene groups obtained recently by this method were found to be selective sensors for detection of gold ions and L-cysteine. 32 Our group previously found that B(C 6 F 5 ) 3 as a Lewis acid could catalyze intramolecular cyclization of the hydrosilyl-substituted all-cis-T 4 in the presence of excess water, and several tricyclic ladder-type SQs with varied siloxane side ring sizes (named as "Bat Siloxane" with 8-8-8 or 12-8-12-membered-ring system, Scheme 1) were synthesized.…”
Section: Introductionmentioning
confidence: 94%
“…23–25 Also, the B(C 6 F 5 ) 3 -catalyzed Piers–Rubinsztajn reaction, a transition metal-free approach to preparing well-controlled branched polysiloxanes, 26–29 has recently become a powerful tool for extending hydrosilyl-substituted all- cis -T 4 with methoxybenzene derivatives. 30–32 All- cis -T 4 with pyrene groups obtained recently by this method were found to be selective sensors for detection of gold ions and l -cysteine. 32…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Unno et al published the syntheses of a series of new Janus-type all-cis-T 4 117-130 starting from tetraphenyl-and tetravinyl-substituted Janus T 4 precursors with Si-H moieties through the Piers-Rubinsztajn reaction. 94,95 The Si-H moieties of the Janus precursors were extended to various aryl derivatives. These compounds are potential precursors for hybrid functional materials (Table 9).…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…1,2 The synthesis of siloxanes with a certain well-defined structure has recently become particularly relevant. 3 This approach enables the fine-tuning of the final properties of the end product by forming compounds with a preset structure.…”
Section: Introductionmentioning
confidence: 99%